Voltage Regulatiin in Generating Networks - Mammadzada, Raman (My University, 2026)
To keep the voltage level acceptable is the primary phenomenon of electrical power system and aiming to keep the voltage around acceptable level different load and generation conditions. Acceptable voltage regulation makes power quality, system reliability, and efficiency better [1]. During the long time, the tap changers have been used to regulate voltage in transformers, and capacitor banks are utilized for regulation of reactive power in electrical power systems. Tap-changing transformers: To adjust voltage dynamically in transformer on-load tap changers regulate transformers turn ratios. Shunt capacitor banks: For supporting local voltage and to make power factors better the capacitor banks are explicitly used. Synchronous Condenser: generate reactive power supply and system consistency, crucial for huge- scale system. These ways, in cutting-edge power system, reliability, not including the speed and flexibility is mandatory.[4] The including of distributed Energy sources and connection of them electrical system can cause some problems related with challenges in voltage regulation. At those times mentioned traditional regulation methods were insufficient for electrical grids and high integrated Distributed energy sources.
Keywords: Electric power distribution.; Reactive power (Electrical engineering).; Capacitor banks (Electric power systems).; Transformers (Electricity) -- Tap changers.; Electric power systems -- Voltage regulation.